Semantics in MH17 tragedy newspaper news - Sha'ri, Sharil Nizam; Yaakob, Nor Azuan; Hassan, Mohd Hazreen Shah; Suhaimi, Mohamad Suhaizi; Che Ramely, Nor Azira; Seruji, Zuraini; Abd Ghani, Rahmah (Human Resource Management Academic Research Society, 2020)
This study is an observation of the use of semantic elements to online newspaper news about the plane crash that has claimed many lives, namely the MH17 Tragedy. The important purpose is to look at the problem of ambiguity of meaning that occurs. In addition, this study also explains the use of semantic elements in newspaper news that can cause changes in the original meaning according to the context of the sentence used. as the main source of information. This study focuses primarily on semantics in online newspaper news by using structural semantic theory approach by (Katz, 1972). This theory emphasizes the meaning of each word based on the sentence used. To achieve that goal, the study was based on identifying semantics and newspaper news. Next make a comparison between the newspaper and describe the semantic meaning in the newspaper news. Through this study, the researcher has used two main newspapers, namely Berita Harian and Utusan Malaysia. A total of 14 newspapers were used as study data, namely seven newspapers were from Berita Harian and seven more were from Utusan Malaysia. Next, the researcher only selected six newspapers to explain the meaning, namely three newspapers from Berita Harian and three more from Utusan Malaysia.